Cu-Zn bimetallic oxide, preparation method thereof and application of Cu-Zn bimetallic oxide in removal of hydrogen sulfide in flue gas

Through the preparation method of Cu-Zn bimetallic oxide, the problem of low desulfurization performance of hydrogen sulfide under low temperature, drying and anaerobic conditions was solved, and the effect of efficient hydrogen sulfide removal was achieved, and the complexity of the load carrier and low saturated sulfur capacity were overcome. The problem of this problem significantly improves the removal rate and capacity of hydrogen sulfide.

CN119281288APending Publication Date: 2025-01-10XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478268.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art has low selective desulfurization performance on hydrogen sulfide under low temperature, drying and anaerobic conditions, and the loaded carrier improves the preparation process of metal dispersion of adsorbents, with low theoretical value of saturated sulfur capacity, making it difficult to develop high-reactive large sulfur. Capacity adsorbent.

Method used

Using the preparation method of Cu-Zn bimetallic oxide, the copper salt and zinc salt are mixed in an alcohol solution, added with ethanolamine solution and stirred vigorously and heat treatment to form a three-dimensional Cu-Zn bimetallic oxide, which increases sulfur capacity and desulfurization. efficiency.

Benefits of technology

It has achieved efficient removal of hydrogen sulfide at a concentration of 1 to 500 ppm under low temperature conditions, significantly improved saturated sulfur capacity, simulated hydrogen sulfide removal rate and complete penetration time with an initial concentration of 100 ppm is significantly better than existing copper-zinc oxide materials. Increased the utilization rate of active sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281288A_ABST
    Figure CN119281288A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-Zn bimetallic oxide, a preparation method thereof and application of the Cu-Zn bimetallic oxide in flue gas hydrogen sulfide removal, and belongs to the technical field of flue gas hydrogen sulfide removal. According to the preparation method of the Cu-Zn bimetallic oxide disclosed by the invention, the Cu salt and the zinc salt are subjected to one-step induction through ethanolamine to form a Cu-Zn bimetallic hydroxide material with a structure, the sulfur capacity is improved by adjusting the space structure of the metal oxide, and meanwhile, another metal oxide is doped to play a positive role in desulfurization efficiency at room temperature. The method provided by the invention overcomes the problem of complex preparation of an adsorbent for improving metal dispersion through a load carrier, has the defect of low theoretical value of saturated sulfur capacity, increases the utilization rate of active sites of metal oxides, and has very wide application prospects in the aspect of treating hydrogen sulfide gas pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flue gas hydrogen sulfide removal, and specifically relates to a Cu-Zn bimetallic oxide and a preparation method thereof and application thereof in flue gas hydrogen sulfide removal. Background Art

[0002] At present, energy shortage and environmental pollution have become huge challenges for the efficient and sustainable development of metallurgy and chemical industry. Although efforts are being made around the world to develop clean resources, it is still far from large-scale industrial application. Fossil fuels such as coal are still the most important power energy sources due to their low cost and large reserves. However, hydrogen sulfide (H2S), as a toxic component, is commonly found in industrial flue gas after incomplete combustion of various fossil fuels. H2S is released into the natural atmosphere, causing environmental pollution and endangering human health. As the main source of H2S production, the metallurgical and chemical industries have been strictly required to carry out deep desulfurization. Although the concentration of hydrogen sulfide in industrial gases is low, the amount of H2S produced in actual industry is huge. In addition, industrial derivative gases, such as blast furnace gas and chemical gas, can be reused due to considerable heat energy and high pressure. At the same time, in order to avoid corrosion of metal equipment, poisoning of downstream catalysts and environmental pollution, H2S in these gases must be removed to a level of one part per million before use. In view of the existing energy situation and environmental needs, the efficient and clean utilization of fossil energy such as coal has become an important issue that needs to be solved urgently.

[0003] In recent years, various desulfurizers have been widely explored to capture H2S in the presence of oxygen over a wide temperature range, and transition metal oxides and rare earth oxides loaded on various porous materials have shown satisfactory desulfurization performance under medium and high temperature conditions. However, in the absence of oxygen, the performance of these adsorbents drops rapidly to below 50 mg / g. In fact, it has been recognized that metal oxide adsorbents act as catalysts for capturing H2S in the presence of oxygen. In addition, a large number of studies have also demonstrated that the desulfurization performance of adsorbents under dry conditions is much lower than that in the presence of water vapor. It is reported that the presence of water in the desulfurization system has a positive effect and has been shown to promote the hydrolysis of H2S. However, there is a lack of research on selective desulfurization under low temperature, dry, and anaerobic conditions, which is a more difficult problem.

[0004] Coke oven gas (COG) is an important byproduct produced during the coking process in the steel industry. It is mainly composed of hydrogen, methane and carbon monoxide, which makes it a high calorific value gas for industrial furnaces. However, various sulfur-containing pollutants, such as thiophene, carbon disulfide, hydrogen sulfide (H2S), etc., must be removed from coal before combustion. First, organic sulfides are converted into H2S by catalytic hydrolysis, and then a desulfurizer is used to remove H2S. The catalytic hydrolysis of COG usually occurs above 150°C, while the removal of H2S is usually below 60°C. Therefore, it is crucial to develop a desulfurizer that can efficiently remove H2S at room temperature. Transition metal catalysts have attracted much attention due to their excellent redox ability and high activity. Studies have shown that copper oxide exhibits the highest sensitivity to H2S at low temperatures and can be used as a sensitive layer for H2S detectors. However, the lack of self-structure limits further improvements in conversion rates. Many scholars have adopted the method of dispersing active components by loading metal oxides on porous SiO2 (MCM-41, SBA-15, KIT-6) or silicate molecular sieves (ZSM-5, 4A molecular sieve zeolite) to obtain higher adsorption rates and smaller diffusion resistance. However, it is worth noting that the theoretical value of the saturated sulfur capacity of the adsorbent with a carrier is lower than that of the adsorbent without a carrier. So far, it is still a challenge to synthesize adsorbents with high reactivity and large sulfur capacity. Therefore, it is of great significance to develop a bimetallic adsorbent with good desulfurization / regeneration ability for coal gas desulfurization. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a Cu-Zn bimetallic oxide and a preparation method and flue gas hydrogen sulfide removal application, so as to solve the defects of the prior art that the preparation process of the adsorbent metal dispersion is complicated and the theoretical value of the saturated sulfur capacity is low by loading the carrier to improve the adsorbent.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention discloses a method for preparing a Cu-Zn bimetallic oxide, comprising the following steps:

[0008] 1) adding copper salt and zinc salt to the alcohol solution and mixing them thoroughly to obtain a mixed solution;

[0009] 2) adding the ethanolamine solution to the mixed solution to obtain a slurry, vigorously stirring the slurry to fully react and then crystallizing it, and then centrifuging, washing, and drying the product to obtain a Cu-Zn double metal hydroxide;

[0010] 3) The Cu-Zn double metal hydroxide is heat treated to obtain a three-dimensional Cu-Zn bimetallic oxide.

[0011] Preferably, in step 1), the molar ratio of copper salt to zinc salt is (1-4):(1-4); the alcohol solution is prepared by ethanol and water in a volume ratio of 1:(2-4); the dosage ratio of the mixed salt of copper salt and zinc salt to ethanol and water is 0.04 mol:1 mL:(2-4) mL.

[0012] Preferably, in step 1), the copper salt is copper chloride, copper nitrate or the like, and the zinc salt is zinc chloride, zinc nitrate or the like.

[0013] Preferably, in step 2), the ethanolamine solution is prepared by mixing ethanolamine and ethanol / water mixed solution in a volume ratio of 1:(8-12); the dosage ratio of the mixed salt of copper salt and zinc salt to ethanolamine is 0.04 mol:5 mL.

[0014] Preferably, in step 2), the slurry is vigorously stirred at 25° C. for 4 to 8 hours. The purpose of the vigorous stirring is to form a bimetallic oxide material in which copper and zinc are evenly distributed.

[0015] Preferably, in step 2), drying is carried out at 60-70°C. Drying at a lower temperature range can retain more active sites in the material, especially drying at 60°C can ensure that the material is dried and the active sites of the material are fully retained.

[0016] Preferably, in step 3), the Cu-Zn double hydroxide is heat treated in a nitrogen atmosphere at a temperature of 300-500°C.

[0017] The invention also discloses a Cu-Zn bimetallic oxide prepared by the preparation method, wherein copper and zinc are evenly distributed.

[0018] The invention also discloses the application of the Cu-Zn bimetallic oxide in preparing a hydrogen sulfide removing agent.

[0019] Preferably, the Cu-Zn bimetallic oxide can efficiently remove hydrogen sulfide from polluted gas having a concentration of 1 to 500 ppm of hydrogen sulfide under low temperature conditions.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The preparation method of the Cu-Zn bimetallic oxide disclosed in the present invention is to induce the formation of a Cu-Zn bimetallic hydroxide material with a structure of copper salt and zinc salt by ethanolamine in one step, to increase the sulfur capacity by adjusting the spatial structure of the metal oxide, and to play a positive role in the desulfurization efficiency at room temperature by doping two metal oxides at the same time. The present invention particularly selects copper-containing and zinc-containing compounds, which have a strong chemical adsorption effect on hydrogen sulfide. Compared with a single metal oxide material, the copper-zinc bimetallic oxide synthesized by the present invention has a higher specific surface area, which can make hydrogen sulfide quickly dispersed to the solid surface during the removal process, thereby improving the removal rate of sulfide. At the same time, compared with a single metal oxide, the bimetallic oxide not only provides more active sites, but also leads to charge compensation due to the uneven distribution of multivalent charges of the bimetallic oxide, resulting in the diffusion of anions and the generation of vacancies, accelerating the transfer and diffusion of sulfur and active atoms, and increasing the removal efficiency of hydrogen sulfide, thereby achieving the ideal effect of removing hydrogen sulfide in flue gas. The method of the present invention overcomes the problem of complex preparation of adsorbents for improving metal dispersion through loading carriers and the disadvantage of low theoretical value of saturated sulfur capacity, increases the utilization rate of active sites of metal oxides, and has very broad application prospects in treating hydrogen sulfide gas pollution.

[0022] The present invention also discloses a Cu-Zn bimetallic oxide prepared by the preparation method of the Cu-Zn bimetallic oxide, and an application of a flue gas hydrogen sulfide remover prepared by the Cu-Zn bimetallic oxide. According to relevant experimental results, in the simulated hydrogen sulfide removal rate with an initial concentration of 100 ppm, when the reaction temperature is 150°C, the initial penetration time is 3960 min, the complete penetration time is 6940 min, and the saturated sulfur capacity can reach 773.58 mg / g. The effect of the material is significantly better than the copper-zinc oxide material reported in the current literature, which fully demonstrates that the gas hydrogen sulfide remover prepared by the present invention is used for the removal and purification of hydrogen sulfide in the atmosphere, and has a high removal efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a physical picture of the Cu-Zn bimetallic oxide prepared in Example 1;

[0024] Figure 2 The removal effect of Cu-Zn bimetallic oxide on hydrogen sulfide;

[0025] Figure 3 A comparison diagram of the Cu-Zn bimetallic oxide prepared in Example 3 and the copper-zinc oxide reported in the literature;

[0026] Figure 4 A comparison diagram of the Cu-Zn bimetallic oxide prepared in Example 3 and the copper-zinc oxide reported in the literature;

[0027] Figure 5The desulfurization curve and sulfur capacity diagram of copper-zinc bimetallic oxide;

[0028] Figure 6 This is the adsorption curve of Cu-Zn bimetallic oxide for hydrogen sulfide. DETAILED DESCRIPTION

[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0030] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0031] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0032] Example 1

[0033] A method for preparing a Cu-Zn bimetallic oxide comprises the following steps:

[0034] 1) Copper chloride (0.04 M) and zinc chloride (0.08 M) were dissolved in 375 mL of ethanol and deionized water (v / v = 1 / 4) and stirred vigorously for 10 min to form a homogeneous solution.

[0035] 2) Ethanolamine (15 mL) was dissolved in 180 mL of deionized water / ethanol (v / v=1 / 2), and then the ethanolamine mixed solution was dropped into the homogeneous solution and vigorously stirred at 25°C for 6 h.

[0036] 3) The above materials were washed with deionized water and ethanol for 3 times and dried at 60°C for 12 h.

[0037] 4) The dried material obtained above was ground and calcined at 400° C. for 2.5 h under a nitrogen atmosphere to obtain a Cu-Zn bimetallic oxide.

[0038] Figure 1 The physical picture of the Cu-Zn bimetallic oxide material prepared in this embodiment is as follows: Figure 1 It can be seen that the Cu-Zn bimetallic oxide material prepared in this embodiment has a fluffy texture and a large specific surface area, which is conducive to the adsorption of pollutants.

[0039] Figure 2 The TEM results of the Cu-Zn bimetallic oxide material prepared in this example are as follows: Figure 2 It can be seen that the copper and zinc in the material prepared in this example are evenly distributed and have excellent metal-based adsorption sites, which is conducive to the adsorption of pollutants.

[0040] Example 2

[0041] A method for preparing a Cu-Zn bimetallic oxide comprises the following steps:

[0042] 1) Copper chloride (0.04 M) and zinc chloride (0.08 M) were dissolved in 375 mL of ethanol and deionized water (v / v = 1 / 4) and stirred vigorously for 10 min to form a homogeneous solution.

[0043] 2) Ethanolamine (15 mL) was dissolved in 180 mL of deionized water / ethanol (v / v=1 / 2), and then the ethanolamine mixed solution was dropped into the homogeneous solution and vigorously stirred at 25°C for 8 h.

[0044] 3) The above materials were washed with deionized water and ethanol for 3 times and dried at 60°C for 10 h.

[0045] 4) The dried material obtained above was ground and calcined at 300° C. for 5 h under a nitrogen atmosphere to obtain a Cu-Zn bimetallic oxide.

[0046] Figure 3 The adsorption curve of hydrogen sulfide by the Cu-Zn bimetallic oxide prepared in this embodiment is as follows. In the simulated hydrogen sulfide removal rate with an initial concentration of 100 ppm, when the reaction temperature is 25 degrees Celsius, the initial penetration time is 158.5 minutes, the complete penetration time is 1890 minutes, and the saturated sulfur capacity can reach 146.30 mg / g. At present, the performance of removing hydrogen sulfide at room temperature is generally lower than 90 mg / g. It can be seen that the Cu-Zn bimetallic oxide material prepared in this embodiment has a significant effect on hydrogen sulfide removal.

[0047] Example 3

[0048] A method for preparing a Cu-Zn bimetallic oxide comprises the following steps:

[0049] 1) Copper chloride (0.06 M) and zinc chloride (0.06 M) were dissolved in 375 mL of ethanol and deionized water (v / v = 1 / 4) and stirred vigorously for 10 min to form a homogeneous solution.

[0050] 2) Ethanolamine (20 mL) was dissolved in 180 mL of deionized water / ethanol (v / v=1 / 2), and then the ethanolamine mixed solution was dropped into the homogeneous solution and vigorously stirred at 25°C for 4 h.

[0051] 3) The above material was washed with deionized water and ethanol for 3 times and dried at 70°C for 8 h.

[0052] 4) The dried material obtained above was ground and calcined at 400° C. for 1.5 h under a nitrogen atmosphere to obtain a Cu-Zn bimetallic oxide.

[0053] Figure 4 This is the adsorption curve of the Cu-Zn bimetallic oxide prepared in this embodiment for hydrogen sulfide. In the simulated hydrogen sulfide removal with a reaction temperature of 150°C and an initial concentration of 100 ppm, the material's sulfur penetration capacity can reach 459.04 mg / g. It can be seen that the Cu-Zn bimetallic oxide material prepared in this embodiment has a significant hydrogen sulfide removal effect, which is better than the desulfurization performance of other copper-zinc oxide materials at the same reaction temperature reported in the literature. Figure 4 The materials prepared by other references are marked as [1], [2], [3], [4] and [5]. The specific reference sources are as follows:

[0054] [1]. Kumar, P.; Sung, C.-Y.; Muraza, O.; Cococcioni, M.; Al Hashimi, S.; McCormick, A.;

[0055] [2].Elyassi,B.;Wahedi,Y.A.;Rajabbeigi,N.;Kumar,P.;Jeong,J.S.;Zhang,X.;Kumar,P.;Balasubramanian,V.V.;Katsiotis,M.S.;Andre Mkhoyan,K.;Boukos,N.;Hashimi,S.A.;Tsapatsis,M.,A high-performance adsorbent for hydrogen sulfideremoval.Microporous Mesoporous Mater.2014,190,152-155

[0056] [3].Barelli,L.;Bidini,G.;Micoli,L.;Sisani,E.;Turco,M.,13X Ex-Cuzeolite performance characterization towards H2S removal for biogas use inmolten carbonate fuel cells.Energy 2018,160,44-53.

[0057] [4].Rezaei,S.;Avila,A.M.;Kuznicki,S.M.,Chemisorption of H2S onCopper-ETS-2:Experiment and Modeling of a Packed Column.J.Nanosci.Nanotechnol.2018,18,(11),7882-7888.

[0058] [5].Shuoyang Liang,Bo Peng,Shiye Liu,Weidong Zhang,Min Guo,FangqinCheng,and Mei Zhang.,Low-Temperature Highly Efficient and Selective Removalof H2S over Three-Dimensional Zn–Cu-Based Materials in an AnaerobicEnvironment.Environmental Science&Technology 2020,54(10),5964-5972.

[0059] Example 4

[0060] A method for preparing a Cu-Zn bimetallic oxide comprises the following steps:

[0061] 1) Copper chloride (0.08 M) and zinc chloride (0.04 M) were dissolved in 375 mL of ethanol and deionized water (v / v = 1 / 3) and stirred vigorously for 20 min to form a homogeneous solution.

[0062] 2) Ethanolamine (20 ml) was dissolved in 180 mL of deionized water / ethanol (v / v=1 / 2), and then the ethanolamine mixed solution was dropped into the homogeneous solution and vigorously stirred at 25°C for 6 h.

[0063] 3) The above material was washed with deionized water and ethanol for 3 times and dried at 65°C for 9 h.

[0064] 4) The dried material obtained above was ground and calcined at 400° C. for 2 h under a nitrogen atmosphere to obtain a Cu-Zn bimetallic oxide.

[0065] Figure 5 The adsorption curve of the Cu-Zn bimetallic oxide prepared in this embodiment for hydrogen sulfide and its sulfur capacity diagram show that in the simulated hydrogen sulfide removal experiment with a reaction temperature of 150°C and an initial concentration of 100 ppm, the Cu-Zn bimetallic oxide material prepared in this embodiment has a penetration sulfur capacity of up to 459.04 mg / g, and the hydrogen sulfide removal effect of the material is significant, which is better than the desulfurization performance of single copper oxide and zinc oxide prepared at the same reaction temperature of 400°C.

[0066] Example 5

[0067] A method for preparing a Cu-Zn bimetallic oxide comprises the following steps:

[0068] 1) Copper chloride (0.04 M) and zinc chloride (0.08 M) were dissolved in 375 mL of ethanol and deionized water (v / v = 1 / 4) and stirred vigorously for 30 min to form a homogeneous solution.

[0069] 2) Ethanolamine (20 ml) was dissolved in 180 mL of deionized water / ethanol (v / v=1 / 2), and then the ethanolamine mixed solution was dropped into the uniform solution and vigorously stirred at 25°C for 10 h.

[0070] 3) The above material was washed with deionized water and ethanol for 3 times and dried at 70°C for 6 h.

[0071] 4) The dried material obtained above was ground and calcined at 350° C. for 2.5 h under a nitrogen atmosphere to obtain a Cu-Zn bimetallic oxide.

[0072] Figure 6The adsorption curve of Cu-Zn bimetallic oxide prepared in this embodiment for hydrogen sulfide is in a simulated hydrogen sulfide removal experiment with a reaction temperature of 25°C and an initial concentration of 100ppm. The Cu-Zn bimetallic oxide material prepared in this embodiment has a sulfur penetration capacity of 12.54mg / g, which is 4.13 times that of the commercially available Banana ZnO (Liuzhou Zinc Products Co., Ltd.) and the commercially available Shanghai Yaoge ZnO (YY-ZnO-Y1). The saturated sulfur capacity of the Cu-Zn bimetallic oxide material prepared in this embodiment is 44.18mg / g, which is 5.32 times that of Banana ZnO and 4.24 times that of Shanghai Yaoge ZnO. In addition, the service life of 600min is much higher than that of Banana ZnO (240min) and Shanghai Yaoge ZnO (190min). Overall, the Cu-Zn bimetallic oxide material prepared in this example has a significant effect on hydrogen sulfide removal, which is better than the desulfurization performance of commercially available zinc oxide.

[0073] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a Cu-Zn bimetallic oxide, characterized in that: The following steps are involved: 1) adding copper salt and zinc salt to the alcohol solution and mixing them thoroughly to obtain a mixed solution; 2) adding the ethanolamine solution to the mixed solution to obtain a slurry, vigorously stirring the slurry to fully react and then crystallizing it, and then centrifuging, washing, and drying the product to obtain a Cu-Zn double metal hydroxide; 3) The Cu-Zn double metal hydroxide is heat treated to obtain a three-dimensional Cu-Zn bimetallic oxide.

2. The method for preparing the three-dimensional Cu-Zn bimetallic oxide according to claim 1, characterized in that: In step 1), the molar ratio of copper salt to zinc salt is (1-4):(1-4); the alcohol solution is prepared by ethanol and water in a volume ratio of 1:(2-4); the dosage ratio of the mixed salt of copper salt and zinc salt to ethanol and water is 0.04 mol:1 mL:(2-4) mL.

3. The method for preparing the three-dimensional Cu-Zn bimetallic oxide according to claim 1, characterized in that: In step 1), the copper salt is copper chloride, and the zinc salt is zinc chloride.

4. The method for preparing the three-dimensional Cu-Zn bimetallic oxide according to claim 1, characterized in that: In step 2), the ethanolamine solution is prepared by mixing ethanolamine and ethanol / water mixed solution in a volume ratio of 1:(8-12); the dosage ratio of the mixed salt of copper salt and zinc salt to ethanolamine is 0.04 mol:5 mL.

5. The method for preparing the Cu-Zn bimetallic oxide according to claim 1, characterized in that: In step 2), the slurry is vigorously stirred at 25° C. for 4 to 8 hours.

6. The method for preparing the Cu-Zn bimetallic oxide according to claim 1, characterized in that: In step 2), the drying is carried out at 60-70°C.

7. The method for preparing the Cu-Zn bimetallic oxide according to claim 1, characterized in that: In step 3), the Cu-Zn double hydroxide is heat treated in a nitrogen atmosphere at a temperature of 300-500°C.

8. The Cu-Zn bimetallic oxide prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Copper and zinc are evenly distributed.

9. Use of the Cu-Zn bimetallic oxide according to claim 8 in preparing a hydrogen sulfide remover.

10. The use according to claim 9, characterized in that The Cu-Zn bimetallic oxide can efficiently remove hydrogen sulfide from polluted gas with a concentration of 1 to 500 ppm of hydrogen sulfide under low temperature conditions.